Factors determining low deforestation: the Bolivian Amazon - Kaimowitz, D. (1997)
Determinants of low deforestation in Bolivia are analysed, based on the Bolivian experience and general deforestation literature, and lessons are drawn for other countries with low deforestation. Weak domestic demand for agricultural products and poor transportation infrastructure are the principal causes of low deforestation. Weak domestic demand is related to small population and low per capita income, and poor transportation infrastructure is a function of a country's low capacity for investment in infrastructure and political factors. Production for export plays an important role in deforestation in these contexts, and is influenced by policies such as road building, appreciated exchange rates and subsidies for commercial agriculture. Factors influencing land clearing by poor families are less relevant. Political and institutional factors deserve greater attention than they have received in previous deforestation literature.